A nucleoside-modified mRNA vaccine prevents enterovirus A71 infection in mouse model - Chi, Fengyu; Zhang, Xu; Zhang, Dong; Zhu, Airu; Zhuang, Zhen; Zhang, Zhaoyong; Zhang, Zhenjie; Quan, Chuansong; Nie, Kaixiao; Li, Juan; Yin, Chunhong; Tong, Jie; et al. (Frontiers in Immunology, 2025)
IntroductionHuman Enterovirus A71 (EV-A71) is the primary pathogen responsible for severe hand, foot, and mouth disease (HFMD). Vaccination plays a crucial role in controlling its spread. Although inactivated vaccines have been approved, there is growing interest in developing new candidates using advanced platforms. mRNA vaccines, widely used for enveloped viruses, are less studied for non-enveloped viruses like EV-A71. This study investigates the potential of an mRNA vaccine targeting the EV-A71 VP1 protein.MethodsA nucleoside-modified mRNA vaccine encoding the VP1 protein of EV-A71, encapsulated in lipid nanoparticles (LNPs), was developed. Immunogenicity and protective efficacy were evaluated in BALB/c and neonatal A129 mice, respectively. Immune responses were assessed by ELISA, micro-neutralization assays, ELISpot, and intracellular cytokine staining (ICS). Passive protection was tested by transferring immune sera to neonatal mice challenged with EV-A71.ResultsThe VP1 mRNA-LNP vaccine elicited robust humoral and cellular immunity, including high levels of VP1-specific IgG, neutralizing antibodies, and a Th1-biased T-cell response. Notably, the mRNA vaccine outperformed the inactivated vaccine in eliciting cellular immunity. Immune sera provided complete protection against lethal EV-A71 challenge, significantly reducing viral load and pathology.DiscussionThis study demonstrates that the mRNA vaccine exhibits significant potential for combating non-enveloped viruses. These findings highlight the promising role of mRNA platforms in advancing vaccine development against non-enveloped viral pathogens, offering new avenues for future research and clinical applications.